2018
DOI: 10.1038/s41388-018-0168-5
|View full text |Cite
|
Sign up to set email alerts
|

PARP10 suppresses tumor metastasis through regulation of Aurora A activity

Abstract: ADP-ribosylation, including poly-ADP-ribosylation (PARylation) and mono-ADP-ribosylation (MARylation), is a multifunctional post-translational modification catalyzed by intracellular ADP-ribosyltransferases (ARTDs or PARPs). Although PARylation has been investigated most thoroughly, the function of MARylation is currently largely undefined. Here, we provide evidences that deficiency of PARP10, a mono-ADP-ribosyltransferase, markedly increased the migration and invasion of tumor cells through regulation of epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 34 publications
0
52
1
1
Order By: Relevance
“…While we cannot exclude an impact of this process on the tumor-promoting activity of PARP10, our data clearly show that PARP10 enhances replication fork elongation at the molecular level, thus strongly arguing that replication stress suppression through TLS engagement is a major component of the oncogenic activity of PARP10. Another recent paper described a role for PARP10 in cell motility through regulating Aurora A activity (13). Interestingly, the authors also created PARP10-knockout HeLa cells and found increased cell motility in vitro, and increased metastasis in vivo (using an experimental approach in which they injected the HeLa cells in the tail vein of Balb/C mice and measured lung metastases).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we cannot exclude an impact of this process on the tumor-promoting activity of PARP10, our data clearly show that PARP10 enhances replication fork elongation at the molecular level, thus strongly arguing that replication stress suppression through TLS engagement is a major component of the oncogenic activity of PARP10. Another recent paper described a role for PARP10 in cell motility through regulating Aurora A activity (13). Interestingly, the authors also created PARP10-knockout HeLa cells and found increased cell motility in vitro, and increased metastasis in vivo (using an experimental approach in which they injected the HeLa cells in the tail vein of Balb/C mice and measured lung metastases).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently it has been proposed to be important for the G1/S cell cycle transition (9) as well as for caspase-dependent apoptosis (10). More recently, it was shown that PARP10 can suppress cytokineinduced activation of the NFκB pathway (11), and plays roles in mitochondrial oxidation (12) and cell migration (13).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we identi ed Aurora A as a functional partner of PARP10 through tandem a nity puri cation [13]. In addition to Aurora A, RNF114, a ubiquitin E3 ligase [22], was found in the PARP10 complex, suggesting that RNF114 might also be a PARP10-interacting protein.…”
Section: Rnf114 Is a Newly Discovered Partner Of Parp10mentioning
confidence: 99%
“…transcriptional regulation [7,8], the unfolded protein response [9], DNA repair [10], insulin secretion [11], immunity [12] and tumour development [13]. While much is known about the cellular roles of PARPs that catalyse PARylation, the function of the PARPs that catalyse MARylation is substantially less understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation